2017
DOI: 10.1097/inf.0000000000001380
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Early Corticosteroid Therapy in Management of Pediatric Septic Shock in Pediatric Intensive Care Patients

Abstract: Early use of corticosteroid in patients with septic shock might shorten the shock reversal time without increase in mortality or superinfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 25 publications
0
29
0
3
Order By: Relevance
“…A small pilot RCT (Steroids in Fluid and/or Vasoactive Infusion Dependent Pediatric Shock, STRIPES) demonstrated the feasibility of a larger RCT to address the role of corticosteroids for the treatment of pediatric shock [44]. Since the publication of the Cochrane meta-analysis in 2015, a few small studies of early corticosteroid therapy in patients with pediatric septic shock and adult patients with sepsis-associated ARDS have been published [45][46][47] but the results are consistent with our current recommendations.…”
Section: Rationalementioning
confidence: 99%
“…A small pilot RCT (Steroids in Fluid and/or Vasoactive Infusion Dependent Pediatric Shock, STRIPES) demonstrated the feasibility of a larger RCT to address the role of corticosteroids for the treatment of pediatric shock [44]. Since the publication of the Cochrane meta-analysis in 2015, a few small studies of early corticosteroid therapy in patients with pediatric septic shock and adult patients with sepsis-associated ARDS have been published [45][46][47] but the results are consistent with our current recommendations.…”
Section: Rationalementioning
confidence: 99%
“…At least one pediatric [320] and several adult [321] interventional trials examining adjunctive corticosteroids for septic shock have concluded that this drug class hastens resolution of shock. Of the four adult, high-quality contemporary RCTs, two reported a mortality reduction and two did not [322][323][324][325][326].…”
Section: Corticosteroidsmentioning
confidence: 99%
“…A recent meta-analysis of 42 RCTs including 9969 adults and 225 children with sepsis found that corticosteroids possibly result in a small reduction in short-term mortality (RR, 0.93; 95% CI, 0.84-1.03), long-term mortality (0.94; 95% CI, 0.89-1.00), faster resolution of shock, and shorter LOS, while also possibly increasing the risk of neuromuscular weakness (RR, 1.21; 95% CI, 1.01-1.52) [327]. Despite a weak recommendation to treat sepsis with hydrocortisone based on the findings noted in the overall meta-analysis [328], the pediatric studies enrolled a combined small number of subjects, reported inconsistent conclusions, had methodologic limitations, and did not demonstrate an overall mortality reduction [320,[329][330][331] (Supplemental Table 19, Supplemental Digital Content 1, http:// links .lww.com/PCC/B139).…”
Section: Corticosteroidsmentioning
confidence: 99%
“…[ 30 ] The characteristics of the control groups in all the included studies were similar to those in the experimental groups, except for steroid use. Most of the studies did not describe the follow-up period, except for 3 studies with 14, 28, and 30 days of follow-up, respectively [ 28 , 30 , 33 ] (Table 1 ). All the studies used an RCT design, and 6 studies adopted a blind method.…”
Section: Resultsmentioning
confidence: 99%